Plants as Model in Biomimetics and Biorobotics: New Perspectives - Mazzolai, Barbara; Beccai, Lucia; Mattoli, Virgilio (Frontiers in Bioengineering and Biotechnology, 2014)
Especially in robotics, rarely plants have been considered as a model of inspiration for designing and developing new technology. This is probably due to their radically different operational principles compared to animals and the difficulty to study their movements and features. Owing to the sessile nature of their lifestyle, plants have evolved the capability to respond to a wide range of signals and efficiently adapt to changing environmental conditions. Plants in fact are able to show considerable plasticity in their morphology and physiology in response to variability within their environment. This results in movements that are characterized by energy efficiency and high density. Plant materials are optimized to reduce energy consumption during motion and these capabilities offer a plethora of solutions in the artificial world, exploiting approaches that are muscle-free and thus not necessarily animal-like. Plant roots then are excellent natural diggers, and their characteristics such as adaptive growth, low energy consumption movements, and the capability of penetrating soil at any angle are interesting from an engineering perspective. A few examples are described to lay the perspectives of plants in the artificial world.